Chemical And Biological Studies On The Essential Oils And Extracts From Dryobalanops Spp. - Haslina, Marzoki (Universiti Malaysia Sarawak (UNIMAS), 2005)
This study was perfom1ed to characterized the chemical composition of essential oils and methanol extractives from Dryobalanops spp. Toxicity testing of essential oils toward brine shrimp, Artemia salina and also biological activity of methanol crude extract on two species of fungi were also evaluated. The essential oils was obtained by hydrodistillation and analysed by Gas Chromatography/Flame Ionization Detector (GC/FID) and Gas Chromatography/Mass Spectrometer (GC/MS). Sesquiterpene (44.4%), aromadendrene (37.64 %) in sapwood 2 and B-selinene (11.38 %) in bark were tend to be the major components in essential oils from Dryobalanops SPP. The alcohol represent 30.6% of the total oils with B-eudesmol 24.72 % and (E)-nerolidol 5.26% and caryophyllene alcohol 10.78 % were the major content in sapwood 1. The extractives obtained by methanol extraction was fractionated by column chromatography. The biological activity testing showed that the essential oils have no significance toxicity against brime shrimp. However, the methanol extract from Dryobalanops spp have shown a moderate anti-fungal activity toward two species of fungus.